IBTIKAR TAQNIYAAT AT-TAQYIM LIL MAHARATI AL-LUGHOTI AL-‘AROBIYAH FI ‎KITABI NAHWI AL-KAFI LI SYAIKH AIMAN AMIN ABDUL GHONI - Hafidzotun Nafi'ah; Umi Baroroh; Aisyatul Hanun (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
This research aims to analyze the assessment techniques in the book Nahwu Al-Kafi by Syaikh Aiman Amin Abdul Ghoni, then provide innovations in assessing Arabic language skills, which consist of listening, reading, speaking and writing skills. This research was studied using qualitative methods, while data collection used remote library research. Primary data comes from the book Nahwu Al-Kafi, while secondary data comes from books, journal articles or documents related to this research. The research results show: first, a listening skills test; consists of multiple choices. Second, reading skills test; consists of essay tests, true false, matching and multiple choice. The three speaking skills tests consist of bound speaking and guided speaking. The four writing skills tests consist of imla', bound writing, guided writing and free writing. The innovation in the test form for assessing maharah istima' is answering short entries from a reading. Then in maharah qiro'ah, namely reading the story text and students are expected to be able to summarize the reading text. Then for speaking skills, students present their work in front of the class. Finally, regarding writing skills, students are instructed to rewrite the story presented in their own language.